2015
DOI: 10.1021/acsnano.5b00698
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Angular Dependence of the Raman Response in Black Phosphorus

Abstract: Anisotropic materials are characterized by a unique optical response, which is highly polarization-dependent. Of particular interest are layered materials formed by the stacking of two-dimensional (2D) crystals that are naturally anisotropic in the direction perpendicular to the 2D planes. Black phosphorus (BP) is a stack of 2D phosphorene crystals and a highly anisotropic semiconductor with a direct band gap. We show that the angular dependence of polarized Raman spectra of BP is rather unusual and can be exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

30
403
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(434 citation statements)
references
References 34 publications
30
403
0
1
Order By: Relevance
“…Measurement of bulk flakes has the added advantage of minimizing the well-known degrading oxidation effects of Te-based TMDs [35]. XRD [18,36] as well as studies of other layered TMD materials [37]. The Raman peaks for certain phonon modes show particular sensitivity to x and lattice symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of bulk flakes has the added advantage of minimizing the well-known degrading oxidation effects of Te-based TMDs [35]. XRD [18,36] as well as studies of other layered TMD materials [37]. The Raman peaks for certain phonon modes show particular sensitivity to x and lattice symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…1c, corresponding to the A g 1 , B 2g and A g 2 modes 24 . Following similar analysis done by Riberio et al, 24 we confirm that the long straight edges of the crystal is indeed along the zigzag direction consistent with recent transmission electron microscopy analysis 25 .…”
mentioning
confidence: 99%
“…One of them is Raman active (labeled as A g 2 ) with its measured frequency in the range from 463 to 470 cm −1 and the other one (label as B 2u ) is infrared (IR) active with its frequency from 468 to 470 cm −1 . 4,5,[9][10][11][12] The two modes also exist in monolayer phosphorene, as illustrated in the inset of Figure 1. Raman experiments on few-layer phosphorenes have shown that the frequency shift of the A g 2 mode from that of bulk is about 2-3 cm −1 or smaller.…”
mentioning
confidence: 88%
“…Raman experiments on few-layer phosphorenes have shown that the frequency shift of the A g 2 mode from that of bulk is about 2-3 cm −1 or smaller. 4,5,[9][10][11]13 While there has been no IR measurement on monolayer phosphorene, it is reasonable to expect that the two modes remain nearly degenerate (possibly within a couple of wavenumbers). A recent experiment 9 has observed the splitting of the A g 2 mode in bilayer graphene and proposed that it could be caused by such accidental degeneracy, while other experiments did not report such splitting.…”
mentioning
confidence: 99%
See 1 more Smart Citation